2021
DOI: 10.3389/fmars.2021.645142
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Nearshore Habitat Use of Young of the Year White Sharks Off Southern California

Abstract: Young-of-the-year (YOY) and juvenile-stage white sharks may use southern California nearshore beach habitats more extensively than previously known, within meters of some of the most heavily used beaches in the world. Such knowledge forms a critical component of species management and conservation plans, in addition to public safety and risk mitigation planning. We used data derived from a combination of satellite tag locations (13 animals over 3 years) and passive acoustic monitoring (34 animals over 8 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 56 publications
0
19
1
Order By: Relevance
“…Immature white sharks are known to primarily use coastal habitats, sometimes covering long distances (hundreds of kilometers) between nurseries (Dewar et al, 2004;Harasti et al, 2017;Curtis et al, 2018;Bruce et al, 2019;Anderson et al, 2021). We did not find significant differences in the mean δ 13 C or δ 15 N between juvenile sharks caught inside and outside BSV.…”
Section: Discussioncontrasting
confidence: 55%
“…Immature white sharks are known to primarily use coastal habitats, sometimes covering long distances (hundreds of kilometers) between nurseries (Dewar et al, 2004;Harasti et al, 2017;Curtis et al, 2018;Bruce et al, 2019;Anderson et al, 2021). We did not find significant differences in the mean δ 13 C or δ 15 N between juvenile sharks caught inside and outside BSV.…”
Section: Discussioncontrasting
confidence: 55%
“…Although 10% of tagged sharks were identified at the same locations across more than 1 year, there was no evidence of stability in structure across multiple years, as returning sharks did not form repeated associations at monitored locations in subsequent years. Juvenile white sharks aggregating at nearshore locations, including those in this study, have been demonstrated to exhibit overlapping, restricted area use (Lyons et al, 2013;Anderson et al, 2021a). An individual's tendency toward association may be indicated by the propensity for spatiotemporal overlap and successive return to the same locations (Klimley and Holloway, 1999;Lilly et al, 2020), a trait exhibited in juvenile white sharks (Bruce et al, 2019;Spaet J. L. Y. et al, 2020;Anderson et al, 2021a).…”
Section: Shark Co-occurrence and Group Dynamicsmentioning
confidence: 77%
“…Juvenile white sharks in southern California are known to seasonally aggregate in annually variable, spatially discrete nearshore locations (Lyons et al, 2013;White et al, 2019;Anderson et al, 2021a). The drivers behind these aggregation "hot spot" patterns, and the selection of specific habitat locations over an abundance of comparable available habitat remain unclear, and are not consistently explained by environmental correlates Anderson et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations